Lithuanian historical conception according to Ignas Onacevičius - Šidlauskas, Algirdas (Lietuvos istorijos studijos, 1997)
We know nothing about the manuscript of „Lithuanian History" written by l. Onacevičius, but how he understood history can be understood from his letter to Teodoras Narbutas. In these letters was formed not only his advice to the author of „Lithuanian Nation History," but, as became clear to l. Onacevičius, Lithuanian historical conception as well. According to his opinion, there must be a separate volume for mythology. He was sorry, that there was no list of names nor places. He also articulated his opinion about the rights of the Grand Dukes. According to l. Onacevičius’ opinion, until the end of the 14th century Grand Dukes had absolute power, and only in the time of Jogaila did the power of noblemen come into existence. l. Onacevičius explained that the nobility’s freedom existed in documents, but not in real life. In general, there was no big difference in Lithuania between estates, until the wedding of Jogaila with the Polish queen; this is when the union between Lithuania and Poland began. It seems that l. Onacevičius was also worried about cultural historical problems. He wrote that in the beginning of Žygimantas Augustas’ rule, Mykolas Lietuvis was the first to show the Lithuanian cultural condition. He was sorry that it was impossible to find out any news about Mykolas Lietuvis and, because of this, could not say his real name. l. Onacevičius pointed out that in the time of Žygimantas Augustas, a group of the Samogitians were pagans. In general, the conditions of life were poor, because Lithuanian nobles were against the enlargement of science, trade, and handicraft. Onacevičius’ point of view of history is very similar to that of Joachirnas Lelevelis’ historical understanding. It is possible to say that both historians of Vilnius estimated Lithuania’s past very similarly.